Sodium Alginate/Chitosan-Coated Liposomes for Oral Delivery of Hydroxy-α-Sanshool: In Vitro and In Vivo Evaluation - Fengming Tan; Huan Li; Kai Zhang; Lulu Xu; Dahan Zhang; Yang Han; Jing Han (MDPI AG, 2023)
Background: Hydroxy-α-Sanshool (HAS) possesses various pharmacological properties, such as analgesia and regulating gastrointestinal function. However, the low oral bioavailability of HAS has limited its oral delivery in clinical application. Methods and Results: To enhance its oral bioavailability, a nanocomposite delivery system based on chitosan (CH, as the polycation) and sodium alginate (SA, as the polyanion) was prepared using a layer-by-layer coating technique. The morphology, thermal behavior and Fourier transform infrared spectrum (FTIR) showed that the obtained sodium alginate/chitosan-coated HAS-loaded liposomes (SA/CH-HAS-LIP) with core-shell structures have been successfully covered with polymers. When compared with HAS-loaded liposomes (HAS-LIP), SA/CH-HAS-LIP displayed obvious pH sensitivity and a sustained-release behavior in in vitro studies, which fitted well to Weibull model. In vivo, the half-life of HAS from SA/CH-HAS-LIP remarkably extended after oral administration compared to the free drug. Additionally, it allowed a 4.6-fold and 4.2-fold increase in oral bioavailability, respectively, compared with free HAS and HAS-LIP. Conclusions: SA/CH-HAS-LIP could be a promising release vehicle for the oral delivery of HAS to increase its oral bioavailability.